2015
DOI: 10.1051/0004-6361/201425235
|View full text |Cite
|
Sign up to set email alerts
|

On the occurrence of galaxy harassment

Abstract: Context. Tidal interactions of galaxies in galaxy clusters have been proposed as one potential explanation of the morphology-density relation at low masses. Earlier studies have shown that galaxy harassment is a suitable mechanism for inducing a morphological transformation from low-mass late-type disk galaxies to the abundant early-type galaxies. Aims. The efficiency of tidal transformation is expected to depend strongly on the orbit of a galaxy within the cluster halo. The orbit determines both the strength … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 72 publications
1
54
0
1
Order By: Relevance
“…Simulations show group preprocessing can influence group members, and that the inclination of a galaxy's disk to its orbital plane can influence the efficiency of stellar stripping (Villalobos et al 2012). This same dependence has since been noted in cluster harassment simulations as well (Bialas et al 2015). Indeed a significant fraction of galaxies, that may have suffered effects from the group environment, may be found in clusters by redshift zero (Mihos 2004;McGee et al 2009;De Lucia et al 2012).…”
Section: Introductionsupporting
confidence: 65%
“…Simulations show group preprocessing can influence group members, and that the inclination of a galaxy's disk to its orbital plane can influence the efficiency of stellar stripping (Villalobos et al 2012). This same dependence has since been noted in cluster harassment simulations as well (Bialas et al 2015). Indeed a significant fraction of galaxies, that may have suffered effects from the group environment, may be found in clusters by redshift zero (Mihos 2004;McGee et al 2009;De Lucia et al 2012).…”
Section: Introductionsupporting
confidence: 65%
“…In comparison, a circular orbit near the cluster centre, that spends a much greater fraction of its time where the potential is most destructive, suffers strong mass loss from harassment. Bialas et al (2015) also find that, in addition to orbit, disk inclination with respect to the orbital plane and disk size can also influence the amount of stellar mass lost. Smith et al (2013c) found that most of the mass loss arises from the tides of the cluster potential, with a small additional amount of mass loss (∼ 30%) due to high speed tidal encounters with other cluster galaxies, in agreement with previous studies (Gnedin 2003;Knebe et al 2006).…”
mentioning
confidence: 76%
“…Mastropietro et al 2005;Smith et al 2010;Bialas et al 2015). The cool, thin disks of previous studies are often so thin that they have no known observable counterpart (Sánchez-Janssen et al 2010).…”
Section: The Stellar Distributionmentioning
confidence: 99%
“…Interactions of galaxies with the potential of larger objects have proved capable of transforming their morphology and kinematics on various scales: those of dwarf galaxies orbiting the Milky-Way-like galaxy (Mayer et al 2001;Kazantzidis et al 2011), galaxies in groups (Villalobos et al 2012), and clusters (Mastropietro et al 2005;Bialas et al 2015). One of the factors influencing the final outcome of such a process is the initial inclination of the galaxy disk with respect to its orbit (Villalobos et al 2012;Łokas et al 2015).…”
Section: Introductionmentioning
confidence: 99%